Key periodontal pathogens may mediate potential pathogenic relationships between periodontitis and crohn's disease - Boyang Sun; Ying Wang; Mengmeng Wu; Geng Feng; Ting Guo (BMC, 2024)
Abstract Background Crohn's disease (CD)-associated periodontitis is common. However, the role of periodontal pathogens in the Coexistence of CD and periodontal disease remains unclear. Methods To investigate the potential relationship mediated by periodontal pathogens between periodontitis and CD, we collected salivary samples from healthy participants (H group, n = 12), patients with CD (Ch group, n = 10), patients with periodontitis (Ps group, n = 12), and patients with Coexistence of CD and periodontal disease (Cp group, n = 12) and analyzed them by 16 S rRNA sequencing. Results Patients with Coexistence of CD and periodontal disease had increased levels of Fusobacterium, Actinomyces, Leptotrichia, and Prevotella, which correlated with the severity of periodontitis. Conversely, the levels of Streptococcus, Neisseria, Haemophilus, and Gemella, which decreased in Coexistence of CD and periodontal disease, were negatively correlated with the severity of periodontitis. To further investigate the role of periodontal pathogens in CD development, representative periodontal pathogens causing periodontitis, Porphyromonas gingivalis and Fusobacterium nucleatum, were administered to mice. These pathogens migrate to, and colonize, the gut, accelerating CD progression and aggravating colitis, and even systemic inflammation. In vitro experiments using a Caco-2/periodontal pathogen coculture revealed that P. gingivalis and F. nucleatum increased intestinal permeability by directly disrupting the tight junctions of intestinal epithelial cells. Conclusion Our findings strongly suggest that periodontal pathogens play a role in the relationship between periodontitis and CD. These results provide a basis for understanding the pathogenesis of Coexistence of CD and periodontal disease and may lead to the development of novel therapeutic strategies.